Technology Adoption Model: Is Use/Non-use a Case of Technological Affordances or Psychological Disposition or Pedagogical Reasoning in the Context of Teaching During the COVID-19 Pandemic Period? - Sadeck, Osman (Frontiers in Education, 2022)
The educational implications of Covid-19 have shaken both practitioners and researchers alike. Practitioners were expected to use technologies instantaneously, and this set up trauma in individuals. The ramification of understanding people’s response to why technologies are accepted /not accepted and used/not used has significant implications for education. This conceptual paper sets out the process used to develop a theoretical framework based on the technology acceptance model (TAM). The constructs within the original TAM (Davis, 1986) and extended TAM (Davis et al., 1989), were explored to understand ‘why’ practicing teachers would choose to use technologies for educational purposes. The TAM has been criticised for being simplistic and narrowly focused. Many researchers criticise TAM because their finding cannot be confirmed or that the constructs don't fit their needs. This paper challenges these critiques. This paper challenges such critique. The theoretical framework suggested in this paper represents a view of reality of the relational and influencing effects of variables that potentially moderate or control affective and cognitive responses. It contributes to the existing literature through a comprehensive reviewing of concepts, constructs and Covid-19 ‘event’ contextual realities. The findings offered are that: contextual realities and application often require a grounded theoretical framework to unravel complex questions and answers; the suggested unidirectional influence of perceived ease of use (PEOU) on perceived usefulness (PU) can be challenged through a dispositional rationale; neglecting non-use as a reality severely hampers TAMs applicability in studies focused on theory testing, and TAM provides sufficient flexibility by leaving the doors open for adaptation, and this flexibility is an asset in social science research.